Mathematical Model of Motion of Modifying Powder Particles in the Shielding (Carrier) Gas; IOP Conference Series: Materials Science and Engineering; Vol. 125 : Materials Treatment: Current Problems and Solutions - Kuznetsov M. A. Maksim Aleksandrovich; Kryukov A. V. Artem Viktorovich; Krampit A. G. Andrey Garoldovich; Zernin E. A. Evgeny Aleksandrovich; Sadykov I. D. (2016, 2016)
Title screen